Clinical and Hemodynamic Effects of CPAP-Therapy in Patients with Cardiogenic Pulmonary Edema - M. V. Gorbunova; A. R. Tatarsky; S. L. Babak; L. A. Golubev; A. G. Chuchalin (Общая реаниматология, 2007)
Objective: to evaluate the clinical and hemodynamic effects of CPAP-therapy in the treatment of alveolar cardiogenic pulmonary edema (CPE) in patients with acute myocardial infarction (AMI).Subjects and methods. The open-labeled prospective study included 22 patients (19 males; mean age, 59.2±5.8 years) with CPE that had complicated the course of AMI. Despite the drug and oxygen therapies of CPE for 30 minutes, progressive respiratory and left ventricular failures were an indication for the initiation of CPAP-therapy (7.3±1.2 cm H2O) that was performed, by employing REM-Star apparatuses (Respironics, USA) and Ultra Mirage facial masks (ResMed, Australia). Oxygen, 2 l/min (FiO2 = 40%), was delivered through the mask circuit. Central hemodynamic parameters were measured before and 60 and 180 minutes after the initiation of CPAP-therapy, by using a Swan-Ganz thermodilution cathether (HANDS OFF, model AH-05000-H, ARROW, USA). Arterial and mixed venous blood gas composition was rapidly determined on an automatic gas analyzer (Rapidlab 348, Bayer, USA).Results. Cyanosis and acrocyanosis disappeared and the number of congestive moist rales reduced in the lung in 19 (86.4%) patients during 30-min CPAP-therapy. The patients’ oxygen status changed: the value of PaO2 significantly increased (82.5±2.5 versus 57.4±4.2 mm Hg at the baseline;p<0.05); SaO2 reached the normal values 60 minutes following CPAP-therapy. There was an increase in the cardiac index (3.1±0.2 versus 2.3±0.1 l/min/m2 at the baseline; p<0.05), a decrease in pulmonary wedge pressure (14.4±21 versus 23.6±2.1 mm Hg at the baseline; p<0.05), and synchronism of right and left cardiac performance.Conclusion. CPAP-therapy optimizes treatment of patients with CPE-complicated AMI, results in the normalization of the arterial blood gas composition, significantly diminishes hydrostatic pulmonary capillary pressure, and promotes the synchronism of the right and left hearts.